Persepsi Masyarakat terhadap Penerapan Teknologi Hidroponik dalam Mendukung Ekonomi Masyarakat Mandiri di Kota Tarakan Kalimantan Utara - Machmuddin, Nurlela; Mubarak, Ahmad; Jafar, Rayhana; Jufriadi, Jufriadi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
One of the problems with agriculture in urban areas is that food access is difficult, while soil conditions for agricultural land are limited and less productive. Currently, the whole world is faced with the Covid-19 pandemic, including in urban areas, so that easy access to food and the availability of safe, cheap, healthy, and nutritious food are essential. Urban farming through hydroponic technology is one of the efforts to procure household food independently. It is expected to support the economy of independent communities—this study aims to analyze the levels of public perception of the application of hydroponic technology. The research was conducted in Tarakan City from April to June 2021. Determining respondents was carried out intentionally, considering that the community had obtained information about hydroponic technology. Data analysis that has been used in answering the research objectives is descriptive qualitative data analysis using a Likert scale to measure the level of public perception of hydroponic technology. The story of perception is determined based on respondents' answers about their knowledge of several perceptions about hydroponic technology. The characteristics of the research respondents consisted of an average age of 30 years, the formal education of the respondents graduated from high school, the average number of family members was four people with the main occupation being non-farmers. The results showed that the public had a heightened perception of the application of hydroponic technology (81.11 percent). The highest perception value is found in the perception that plants grown hydroponically are healthier, the quality of the results is maintained, maintenance is easy and more practical. It has a high selling price compared to those grown conventionally.